53.8k views
4 votes
When x = 1, y= 2, z = 3, then find the value of the sum of 5x square , -2x cube y and 3y to the power 4

User AkselK
by
4.8k points

2 Answers

5 votes

Answer:

1305

Explanation:

Equation =
( 5x )^(2) + ( -2x ^(3) )y + ( 3y )^(4)

= (5×1)² + {(-2×1)³}×2 + (3×2)⁴

= (5)² + {-2}³×2 + (6)⁴

= 25 + (-8)×2 + 1296

= 25 + (-16) + 1296

= 25 - 16 + 1296

= 9 + 1296

= 1305

User DeepWebMie
by
4.4k points
1 vote
5(1)^2 = 5 -2(1)^3(2)= -4 3(2)^4 = 48
5 - 4 + 48= 49

The answer is 49
User Trilby
by
5.5k points